Cone Beam Computed Tomography in Orthodontics - Furkan Dindaroğlu; Enver Yetkiner (Galenos Yayinevi, 2016)
The advent of three-dimensional (3D) imaging technology has caused a significant change in the diagnostic approach practiced in dentistry, and in particular, orthodontics. Although conventional imaging methods such as orthopantomography and lateral cephalometric and anteroposterior graphs provide sufficient information in mild to moderate orthodontic anomalies, 3D imaging can be a necessity in severe skeletal anomalies or tooth impactions. Computed tomography (CT) has been frequently used when detailed 3D imaging is necessary despite its relatively high cost, low vertical resolution, and high dose of radiation. In contrast to conventional CT application, the development of cone beam computed tomography (CBCT) technology has had important advantages over the conventional method, such as minimization of the radiation dose, image accuracy, rapid scan time, fewer image artifacts, chair-side image display, and real-time analysis. These advantages have provided dental practitioners the opportunity to benefit more frequently from 3D imaging by relatively diminishing radiation dose considerations, financial burden, and availability, in particular. Therefore, the aim of this review is to highlight the current understanding of CBCT practice in orthodontics and to summarize clinically relevant conditions.